EMOTION BASED ANALYSIS OF TURKISH CUSTOMER OPINIONS - E. Kahya-Ozyirmidokuz; E.A. Stoica (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
Firms should manage their customer feedback so they can adapt to rapid changes in the environment. They have to interact with their customers to understand them and to turn their opinions into useful knowledge. Understanding customers' feelings about a product gives firmS competitive advantage through continuous market monitoring. They can thus generate improving strategies about the system to change perceptions that drive the behaviours of the customers. Firms can view their customers' happiness as a key tool for decision-making. This study calculates online product happiness by using the average emotional valence values of customer opinions. We analyse Turkish opinions about a product over a period of 3 months. We find the averages of the online emotional valence values of the product per month. We also determined the increase in happiness over time. According to the opinion valence values, we found the relations between the documents.